The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1994
DOI: 10.1103/physreva.49.4009
|View full text |Cite
|
Sign up to set email alerts
|

Two-photon emission spectrum of a two-level atom in an ideal cavity

Abstract: The time-dependent two-photon emission spectra of a two-level atom interacting with a single-mode radiation field in an ideal cavity have been studied. The expressions of the system operators as a function of time have been derived based on the two-photon Jaynes-Cummings model and Heisenberg equation. As a result, the theoretical curves of the time-dependent two-photon emission spectra have been given. The features of two-photon emission spectra depend not only on the photon statistical distribution of the ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…It is explicit that the atomic inversion for the field initially in a number state |n 1 , n 2 is strictly periodic and different number states have different Rabi flopping frequency. From (12) it is seen that the transition probability |b n 1 +1,n 2 +1 (t)| 2 is finite when both n 1 = 0 and n 2 = 0. The generated fields in such a case are very much weaker since they are created by spontaneous emission.…”
Section: Two Mode Ladder Modelmentioning
confidence: 97%
See 1 more Smart Citation
“…It is explicit that the atomic inversion for the field initially in a number state |n 1 , n 2 is strictly periodic and different number states have different Rabi flopping frequency. From (12) it is seen that the transition probability |b n 1 +1,n 2 +1 (t)| 2 is finite when both n 1 = 0 and n 2 = 0. The generated fields in such a case are very much weaker since they are created by spontaneous emission.…”
Section: Two Mode Ladder Modelmentioning
confidence: 97%
“…The occurrence of the transformed state |a, n 1 , n 2 corresponds to no interaction whereas the occurrence of the state |b, n 1 + 1, n 2 + 1 admit of interaction in which one photon of mode ω 1 is emitted along with another photon of mode ω 2 , resulting in two-mode process. It is easy to see from (12) that the transition probability and hence the energy emitted depends upon √ (n 1 + 1)(n 2 + 1) in place of √ (n + 1) in J-C model [13] and √ (n + 1)(n + 2) in the two photon single mode J-C model [12,21].…”
Section: Two Mode Ladder Modelmentioning
confidence: 99%
“…In fact, the interaction between a two-level atom and the radiation field is a quantum optical problem that lies at the heart of many problems in laser physics and quantum optics [2][3][4]. Much of theoretical work on the atomic emission spectra is based on the two-photon JCM [5][6][7][8][9][10], Nasreen and Razmi [8] studied the emission spectrum of the atom and the cavity field spectrum, with concentration on the effects of the Stark shift on the spectrum. Ashraf [10] studied the cavity field spectra for various initial fields of the non-degenerate two-photon JCM and showed that a two-peak structure appears for initial coherent and thermal fields.…”
Section: Overviewmentioning
confidence: 99%
“…Cavity-controlled two-photon emission rate from a QW is calculated by a second order process in the time-dependent perturbation theory, similar to that of two-photon transition in a single atom [13]. The general expression for the rate is:…”
Section: Fig 2 Qws In a Vertical Cavity Combined With 2d Photonic Crmentioning
confidence: 99%